Sostenibilidad Financiera en organizaciones textiles de la Economía Popular y Solidaria en el Ecuador - Peláez Moreno, Lenin Ernesto (2023)
The study evaluates the financial sustainability of textile production organizations in the Popular and Solidarity Economy of Ecuador. To achieve this, a model was applied that examines financial sustainability through the dimensions of operations, liquidity, and leverage. The financial statements of 1226 textile associations located in 37 cantons of Ecuador during the period 2019-2021, included in the database of the Superintendence of Popular and Solidarity Economy of Ecuador, were used. The results are presented at the cantonal level and indicate that in nine cantons, organizations were financially sustainable in all three dimensions, while in one canton, organizations exhibited operational and liquidity problems. Additionally, in twenty-seven cantons, associations revealed operational problems. In summary, the results indicate that textile production organizations in the associative sector, included in the Popular and Solidarity Economy of Ecuador, have moderate financial sustainability. The main challenge facing these organizations is operational, due to the lack of income generated by their economic activities, which affects their financial performance and is reflected in a reduction in net assets. From this perspective, the Popular and Solidarity Economy, as an alternative to the market economy, requires a set of conditions in the economic, financial, and political areas to achieve long-term sustainability.